(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article discusses formal stylistic studies in Uzbek literature of the period of independence, their artistic and aesthetic factors, important features of poetry, updated under the influence of Uzbek classical literature and world poetry. The difference between a literary genre and an artistic form is shown using a number of scientific sources and evidence. In recent years, the works of artists who have conducted artistic research in Uzbek literature and their unique aspects will be discussed.